2021
DOI: 10.1002/anie.202111900
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self‐Assembled DNA Nanosystem for Synergistic Chemical and Gene Regulations on Cancer Cells

Abstract: Incorporating multiple molecular interactions within asystem to realize the metabolic reprogramming of cancer cells is prospected to be of great potential in cancer therapy. Herein, we report asupramolecular self-assembled DNAnanosystem, which reprogrammed the cellular antioxidant system via synergistic chemical and gene regulations.I nt he nanosystem, amphipathic telluroether was coordinated with Mn II to selfassemble into micelle,o nw hich as iNrf2 integrated DNA network was assembled. The great electron-don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Li et al. reported a supramolecular DNA nanometer system that interferes with cellular antioxidant systems [18] . Previously, we demonstrated that framework nucleic acids carrying functional DNA segments (single‐ or double‐stranded DNA) can capture intracellular miRNAs in cancer [19] .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Li et al. reported a supramolecular DNA nanometer system that interferes with cellular antioxidant systems [18] . Previously, we demonstrated that framework nucleic acids carrying functional DNA segments (single‐ or double‐stranded DNA) can capture intracellular miRNAs in cancer [19] .…”
Section: Introductionmentioning
confidence: 95%
“…[17] Li et al reported a supramolecular DNA nanometer system that interferes with cellular antioxidant systems. [18] Previously, we demonstrated that framework nucleic acids carrying functional DNA segments (single-or doublestranded DNA) can capture intracellular miRNAs in cancer. [19] In another study, we showed that self-assembled siRNA-loaded DNA nanoparticles could regulate endothelial cell permeability and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, we constructed a supramolecular selfassembled DNA nanosystem, which could enhance the oxidative stress of tumor cells through synergistic chemical and genetic regulation (Figure 4). [23] The synthesized amphiphilic telluride ether was coordinated with Mn 2 + to form a Te/Mn coordination complex (Te/Mn). The cholesterol-modified DNA (I-DNA) anchored on Te/Mn via hydrophobic interaction could initiate cascade clamped hybridization chain reaction (C-HCR) of DNA hairpins (H1 and H2) to form dynamic DNA network.…”
Section: Dna-polymer Nanomaterialsmentioning
confidence: 99%
“…[9] As such, recently researchers have put large efforts to develop combinatorial drug delivery systems which can not only integrate the advantages of each therapeutic modality, but also strengthen the therapeutic effect in a synergistic way, thus reducing the drug dosage and side effects. [10] In combinatorial therapies against cancer, nucleic acid therapeutics including antisense oligonucleotides (ASOs) and small interfering RNAs (siRNAs) [11][12][13] are frequently employed to suppress the expression of tumor-driven oncogenes or drug-resistance-related proteins, which can further enhance the sensitivity and potency of chemotherapeutics to achieve additive therapeutic effects. [14][15][16] Despite great advances, co-delivery of chemo and gene therapeutics for combinatorial therapy still encounters limitations, including unstable drug packages, potential separation of the drugs during the circulation, and the lack of precise control over the gene and chemo drug ratio.…”
Section: Introductionmentioning
confidence: 99%